A study on Seberang Perai Polytechnic lecturers' perception on the integration of digital language lab in the English language lesson / Mohd Khalid Ustati - Ustati, Mohd Khalid (2012)
The installation and upgrading of Digital Language Labs (DLL) from the analogue language laboratories into all Polytechnics institutions in order to improve the students' English language learning experience has received feedback both positive and negative from the polytechnic English Language lecturers. This study explores the perception of Seberang Perai Polytechnic English Language lecturers upon the utilization of DLL and its integration toward their teaching of English for Specific Purposes (ESP). It is also aimed to identify benefits gained by lecturers and students from using digital language lab apart from identifying issues faced by the lecturers and students during DLL sessions that are detrimental in improving polytechnics students' language proficiency. A total of 15 English Language lecturers from Seberang Perai Polytechnics participated in the survey and a total of 7 interviewees were purposively sampled and consented to be interviewed for in-depth perception research. Findings of this mixed method research show that majority of lecturers agree that digital language lab enhances their teaching experiences in a variety of ways consecutively to catch up with the digitally native students yet at the same time informs of various challenges faced in order to integrate DLL into their lesson plan. Apart from addressing on the issues of lecturers' perception, this study also recommends solutions for restructuring the role of the Digital language laboratories such as the need for the establishment of Polytechnic DLL community, construction of related teaching software (theories and practical) and interactive course content that is more tailored toward ESP in order to improve DLL efficiency.